Creative Economy Collaboration in Enhancing the Global Competitiveness of Solo City as an International MICE Destination - Hasna Wijayati; Haryo Kusumo Aji (Lembaga Publikasi Ilmiah Nusantara, 2026)
This study examines how creative economy subsectors in Solo City collaborate to strengthen the city’s global competitiveness as an international MICE (Meetings, Incentives, Conferences, and Exhibitions) destination. Previous studies have largely examined creative economy subsectors separately and have paid limited attention to the integration of collaborative governance and Global Value Chain (GVC) perspectives within the context of MICE development. Using a qualitative descriptive approach, data were collected from seven key informants through semi-structured interviews, focus group discussions, observations, and document analysis. Data were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings show that Solo’s creative economy subsectors significantly strengthen the city’s cultural identity and attractiveness as a MICE destination. However, collaboration among stakeholders remains fragmented and largely event-based, while integration into the global MICE value chain is constrained by weak institutional coordination, limited international networking, and insufficient digital capacity. The study further demonstrates that collaborative governance contributes to value chain upgrading by strengthening institutional coordination, knowledge sharing, and cross-sector collaboration, thereby creating opportunities for process and functional upgrading within the MICE ecosystem. The main contribution of this study lies in integrating Collaborative Governance and Global Value Chain perspectives to explain how collaborative mechanisms facilitate value chain upgrading and enhance the international competitiveness of medium-sized culture-based MICE destinations.